2012
DOI: 10.1038/nature11394
|View full text |Cite
|
Sign up to set email alerts
|

A transcriptomic hourglass in plant embryogenesis

Abstract: Animal and plant development starts with a constituting phase called embryogenesis, which evolved independently in both lineages. Comparative anatomy of vertebrate development--based on the Meckel-Serrès law and von Baer's laws of embryology from the early nineteenth century--shows that embryos from various taxa appear different in early stages, converge to a similar form during mid-embryogenesis, and again diverge in later stages. This morphogenetic series is known as the embryonic 'hourglass', and its bottle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
296
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(329 citation statements)
references
References 29 publications
17
296
2
Order By: Relevance
“…The theoretical basis of genomic phylostratigraphy and detailed phylostratigraphic procedures have been described previously (10,13,(57)(58)(59). Protein coding sequences for Danio rerio (25,638 genes), Drosophila melanogaster (13,413 genes), and Arabidopsis thaliana (27,148 genes) were retrieved from the Ensembl database (version 69) (60).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The theoretical basis of genomic phylostratigraphy and detailed phylostratigraphic procedures have been described previously (10,13,(57)(58)(59). Protein coding sequences for Danio rerio (25,638 genes), Drosophila melanogaster (13,413 genes), and Arabidopsis thaliana (27,148 genes) were retrieved from the Ensembl database (version 69) (60).…”
Section: Methodsmentioning
confidence: 99%
“…For example, TFs are the master regulators of embryonic development in embryophytes and metazoans (9), and analyses of their embryonic transcriptional profiles support the presence of a phylotypic stage in both lineages (10)(11)(12)(13)(14). These studies have also shown that evolutionarily younger genes tend to be expressed at earlier and later stages of development, whereas the transcriptomes of the middle stages (the phylotypic stage) are dominated by ancient genes (10,13). It remains to be investigated how the evolutionary age and the expression patterns of the different TFs shift throughout the ontogeny of these lineages and whether TF expression profiles correlate with the general transcriptome profiles.…”
mentioning
confidence: 99%
“…SASTs . 150 bp (50 codons) were used in KaKs analysis, and KaKs ratios of those SASTs alignments with Ka , 0.5, Ks , 5, and Ka/Ks , 2 were retained for further analysis (Quint et al 2012). Since these filtering processes resulted in , 100 SAST alignments associated with AltTE events, we focused only IntronR, ExonS, AltA, and AltD events for this analysis.…”
Section: Measure Of Selection Pressure On Asmentioning
confidence: 99%
“…The functional relevance of nonconserved microRNAs is the subject of much debate, as they are often reported to be expressed at low levels or during restricted stages of development (Berezikov 2006;Chen and Rajewsky 2007;Liang and Li 2009;Meunier et al 2012;Roux et al 2012). Despite a general positive correlation between sequence conservation and expression, conservation of the protein-coding transcriptome is not uniform across different stages of development (Davis et al 2005;HazkaniCovo et al 2005;Cruickshank and Wade 2008;Roux and Robinson-Rechavi 2008;Domazet-Lošo and Tautz 2010;Kalinka et al 2010;Irie and Kuratani 2011;Kalinka and Tomancak 2012;Quint et al 2012). For example, the protein-coding transcriptome of adult animals has been shown to be less conserved than that of the embryo in both invertebrates and vertebrates (Domazet-Lošo and Tautz 2010).…”
Section: Introductionmentioning
confidence: 99%